Answer:
Z = 34
Step-by-step explanation:
From the series, we have that:
a = -2
a + d = 7
Hence, -2 + d = 7
∴ d = 7 + 2 = 9
a + 2d = X; a + 3d = Y and a + 4d = Z
-2 + 4(9) = Z
∴ Z = 36 - 2 = 34
Answer:
7.9
Step-by-step explanation:
the first thing to do is find the second projection.
16-7 = 9
than we can use a proportion to find BD
7 : BD = BD : 9
BD = √9 x 7 = √63 = 7.9
we have to use the square root because in the proportion BD Is repeated two times. If we don’t use it, we find BD^2
Answer:
3(5y+7)
Step-by-step explanation:
Answer:
What
Step-by-step explanation: I really knowing